Validación del método analítico espectrofotométrico UV/VIS para la cuantificación de alprazolam 0,5 mg en comprimidos - Tarrillo Peralta, Lizbeth Katarini (2017)
The present study aimed to validate the analytical method by UV-VIS spectrophotometry for the quantification of alprazolam 0.5 mg in tablets, by the standard and the sample, also no interference and the analyte is unstable to forced degradation. In the linearity test it was found that, for the standard, the correlation coefficient (r) was 0.9975 and for the (r) method was 0.9999, and the coefficient of determination (r2) was 0.9951 and 0.999 respectively, demonstrating the linearity of the method. Likewise, the method showed accuracy, with no significant difference between the average recovery (98.84%). The precision of the system and method was evaluated, and the coefficient of variation (CV) was found to be 1.1844% and 1.9923% respectively (specification value <2) and 1.79% intermediate precision. It is concluded that the analytical method is specific, linear, accurate and precise, and applicable for the quantification for the application of Alprazolam 0.5 mg tablets